Association of neighborhood level socioeconomic status and patient reported clinical improvement following total shoulder arthroplasty - Caleb Morgan, MD; Amanda Firoved, MOT, OTR; Patrick J. Denard, MD; Justin W. Griffin, MD (JSES International)
Background: Prior studies have demonstrated higher preoperative pain and decreased patient-reported outcomes (PROs) following total shoulder arthroplasty (TSA) in individuals with lower socioeconomic status (SES). The goal of this study was to investigate the rate of clinical improvement following TSA in individuals with differing SES. Methods: Individuals included in this study underwent anatomic or reverse TSA by 2 surgeons between May 2018 and January 2021. Patients were split into 3 SES groups (low, moderate, and high) based on neighborhood SES level as determined by Area Deprivation Index. PROs were collected preoperatively and at 9 weeks, 26 weeks, 1 year, and 2 years postoperatively. Shoulder-specific PROs included the American Shoulder and Elbows Surgeons shoulder score, 10-point visual analog scale for pain, single-assessment numeric evaluation, and Western Ontario Osteoarthritis of the Shoulder Index. The Veterans Rand 12-Item health survey was used to measure overall well-being. We used a mixed-design analysis of variance to determine the interaction of time and improvement in PROs following surgery followed by 1-way mixed-design analysis of variance with post-hoc analysis. Results: One hundred seventy individuals (low SES n = 34, moderate n = 90, high n = 46) met the inclusion criteria and were included in this study. There were no significant differences between groups for body mass index or age at time of surgery. All groups significantly improved from baseline scores on all PROs (P < .001) with the majority of improvement being achieved within the first year after surgery. There were no significant differences in rate of clinical improvement on PROs among the groups when compared to their respective preoperative scores. Significant differences were discovered when comparing groups independent of time with the low- and moderate-SES groups scoring significantly lower on American Shoulder and Elbows Surgeons shoulder score when compared to the high-SES group (P < .01) and the low-SES group reporting significantly higher visual analog scale pain when compared to the high-SES group (P = .034). Conclusion: Individuals with lower SES at the neighborhood level report higher pain and decreased shoulder function both preoperatively and postoperatively following TSA; however, the rate of clinical improvement following surgery in this group is comparable to individuals with higher SES when compared to baseline scores. All groups demonstrated significant improvement following surgery, suggesting TSA remains a successful operation regardless of SES.